(untitled) (Clinics, 2009)
INTRODUCTION: In elderly patients with acute myocardial infarction, very little is known about the role of surgical myocardial revascularization and percutaneous coronary intervention (invasive therapies - IT), especially in the context of long-term outcomes after hospital discharge. METHODS: We analyzed 1588 patients with MI who had been included prospectively in a databank and followed for up to 7.5 years. In this population, 548 patients were >;70 years old (elderly group - EG), and 1040 were